2023
DOI: 10.1515/biol-2022-0560
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavone reduces LPS-induced acute lung injury via increasing aquaporin 1 and aquaporin 5 in rats

Abstract: Acute lung injury (ALI) followed with severe inflammation and oxidative stress. Anti-inflammatory and antioxidant are the properties of aquaporin 1 (AQP1) and aquaporin 5 (AQP5). The goal of this study was to see if soy isoflavone can diminish lipopolysaccharide (LPS)-induced ALI and the underling mechanism. LPS-induced ALI was given to Sprague–Dawley rats 14 days following oophorectomy. One hour before the LPS challenge, estradiol (1 mg/kg) was administered subcutaneously as positive control and soy isoflavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition, it has been found that apoptosis of alveolar macrophages is an important link in the VALI progression. In many cases, such as endogenous or exogenous stimulation, alveolar macrophages can be induced to enter the apoptosis process (18). The increase in the number of apoptosis of alveolar macrophages not only leads to the non-phagocytosis of apoptotic neutrophils but also causes the release of inflammatory mediators and oxidative stress-related products to of the VALIG were reduced than that of the BCG(P<0.05) (Table 4).…”
Section: Relative Expression Of Ampk and Pgc-1α Mrna In Rat Lung Tissuementioning
confidence: 97%
“…In addition, it has been found that apoptosis of alveolar macrophages is an important link in the VALI progression. In many cases, such as endogenous or exogenous stimulation, alveolar macrophages can be induced to enter the apoptosis process (18). The increase in the number of apoptosis of alveolar macrophages not only leads to the non-phagocytosis of apoptotic neutrophils but also causes the release of inflammatory mediators and oxidative stress-related products to of the VALIG were reduced than that of the BCG(P<0.05) (Table 4).…”
Section: Relative Expression Of Ampk and Pgc-1α Mrna In Rat Lung Tissuementioning
confidence: 97%
“…Pre-treatment of rats with increasing concentrations of soy isoflavone resulted in a dose-dependent upregulation of AQP1 and AQP5 mRNA and protein expression. Additionally, soy isoflavone was found to decrease TNF-α, IL-1β, and IL-6 levels, alleviating pulmonary edema and lung damage [ 37 ].…”
Section: Aquaporin Regulators In Experimental Models Of Sepsismentioning
confidence: 99%
“…Table 3 lists the regulators of AQP expression and their effects on experimental sepsis progression. LPS-exposed rats Pre-treatment with increasing concentrations of soy isoflavone resulted in dose-dependent upregulation of AQP1 mRNA and protein, alleviating pulmonary edema and lung damage [37] LPS-exposed rats Hydrogen-rich saline reverses AQP1 mRNA and protein downregulation [38] LPS-exposed rats Selenium treatment resulted in the upregulation of AQP1 protein expression in the kidneys [39] CLP rats MEF2C treatment attenuated the progress of lung injury while upregulating AQP1 mRNA and protein expression [40] CLP rats Emodin pre-treatment significantly increased AQP1 mRNA and protein expression, suppressing sepsis-induced pulmonary apoptosis [26] LPS-exposed HPMECs Silencing HIF1A expression in LPS-induced cells attenuated AQP1 upregulation and regulated the cells' volume increase [41] AQP2 LPS-exposed rats Dexpanthenol increased AQP2 mRNA expression in kidney tissues through the SIRT1 signaling pathway [43] LPS-exposed rats Rhein treatment attenuated the downregulation of AQP2 protein expression in the kidneys [42] LPS-exposed rats Propofol pre-treatment protected the rats from further kidney complications by restoring AQP2 mRNA levels [44] AQP3 CLP rats Ss-31 treatment resulted in decreased protein expression of AQP3 and pulmonary vascular permeability [27] AQP4 LPS-exposed mice TGN-020 treatment resulted in downregulation of AQP4, suppression of inflammatory cytokine production, and better survival rates [75] AQP5 LPS-exposed mice Lipoxin A 4 presents a protective role in lung injury by upregulating AQP5 protein expression in lung tissue [47] LPS-exposed mice Fasudil upregulates AQP5 mRNA and protein levels while eliminating LPS-induced lung edema and preventing LPS-induced pulmonary inflammation [46] LPS-exposed mice Estradiol treatment pre-LPS exposure upregulated AQP5 mRNA and protein levels, reducing oxidative stress and inflammatory responses [36] LPS-exposed rats Hydrogen-rich saline reverses AQP5 mRNA and protein downregulation [38] LPS-exposed rats Pre-treatment with increasing concentrations of soy isoflavone resulted in dose-dependent upregulation of AQP5 mRNA and protein, alleviating pulmonary edema and lung damage [37] CLP rats…”
Section: Aquaporin Regulators In Experimental Models Of Sepsismentioning
confidence: 99%
“…At the therapeutic level, an interesting report focuses on the role of ropivacaine to inhibit/prevent pressure-induced lung endothelial hyperpermeability [ 73 ]. Further, soy isoflavone has been proposed to reduce pulmonary edema in a dose-dependent manner [ 74 ]. Mesenchymal stem cell therapies are also reported as promising therapeutic agents in ARDS [ 75 ].…”
Section: Conclusion and Summary Of Unknown Points To Be Addressed In ...mentioning
confidence: 99%